2019
DOI: 10.9734/acri/2019/v18i130123
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatotoxic Effect of Sildenafil Citrate and Its Combination with Tramadol on Male Wistar Rats is Ameliorated with Vitamin E Supplementation

Abstract: Aims: This study investigated the effect of vitamin E on serum liver enzymes and bilirubin concentrations in male Wistar rats treated with sildenafil citrate (SC) and a combination of SC and tramadol on the background that these drugs cause oxidative damage to the liver. Methods: Thirty male Wistar rats (180-200 g) were randomly divided into six groups (n=5) thus: control (0.2 ml vehicle – olive oil), SC-treated group (Sil) (10 mg/kg of SC), SC+tramadol-treated group (Sil+Tra) (10 mg/kg of SC and 20 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Sildenafil citrate has been reported to reverse biochemical/histopathological changes in the liver due to jaundice and offer hepatoprotective action against drug-induced hepatotoxicity [31,32]. Some other studies have however reported hepatotoxic effects of increasing doses of sildenafil and the combination of sildenafil and tramadol in experimental models [1,33]. Table 2 shows the renal function parameters of the rats after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil citrate has been reported to reverse biochemical/histopathological changes in the liver due to jaundice and offer hepatoprotective action against drug-induced hepatotoxicity [31,32]. Some other studies have however reported hepatotoxic effects of increasing doses of sildenafil and the combination of sildenafil and tramadol in experimental models [1,33]. Table 2 shows the renal function parameters of the rats after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…They attributed the effect to its antioxidant properties, as it significantly decreased thiobarbituric acid reactive substances (TBARs) while increasing glutathione (GSH) and total thiol (T-SH) levels in the tissues evaluated. Other studies have pointed out the risk of increased hepatic and renal damage due to long-term use of tramadol and its combination with sildenafil [15,33].…”
Section: Resultsmentioning
confidence: 99%